2022
DOI: 10.3390/molecules27134055
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Behaviors of Aconitum Alkaloids in Different Concentrations of Aconiti Lateralis Radix Praeparata and Effects of Aconitine in Healthy Human and Long QT Syndrome Cardiomyocytes

Abstract: Aconiti Lateralis Radix Praeparata (Fu Zi) is the processed lateral root of Aconitum carmichaelii Debx, which is widely used in emergency clinics. Poisoning incidents and adverse reactions occur with the improper intake of Fu Zi. Metabolic characteristics of aconitum alkaloids of Fu Zi may vary, and the effects of Fu Zi in healthy and Long QT syndrome (LQTS) patients is unknown. In this experiment, 24 Sprague Dawley rats were randomly divided into three groups: 2.0, 1.0, and 0.5 g/kg dose groups, and blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Despite containing diverse poisonous compounds, several Aconitum spp. has been used in TCM for over 2,000 years, among which A. carmichaelii Debx is the most used (Zhao et al, 2021;Yang et al, 2022). Comprehensive information about the therapeutic index of its alkaloids is unavailable, which has led to several cases of poisoning and death.…”
Section: Metabolism Of Aconitum Alkaloidsmentioning
confidence: 99%
“…Despite containing diverse poisonous compounds, several Aconitum spp. has been used in TCM for over 2,000 years, among which A. carmichaelii Debx is the most used (Zhao et al, 2021;Yang et al, 2022). Comprehensive information about the therapeutic index of its alkaloids is unavailable, which has led to several cases of poisoning and death.…”
Section: Metabolism Of Aconitum Alkaloidsmentioning
confidence: 99%
“…Several studies have demonstrated that alkaloids found in Fuzi have significant anti‐tumor effects (Dai et al, 2023; Fan et al, 2016; Fu et al, 2022; Li et al, 2022; Yu et al, 2021; Zhou et al, 2015). These alkaloids can be divided into three general categories based on structure: diester‐type alkaloids, such as aconitine, mesaconitine, and hypaconitine; monoester‐type alkaloids, such as benzoyl aconitine, benzoyl mesaconitine, and benzoyl hypaconitine; and alcohol amine‐type alkaloids, such as aconine, mesaconine, and hypaconine, among which diester‐type alkaloids are considered the active and toxic components of Fuzi (Gao et al, 2022; Jang et al, 2022; Jiang et al, 2022; Jin et al, 2022; Punia et al, 2022; Tian et al, 2022; Wang et al, 2022; Xin et al, 2022; Yang et al, 2022). The most abundant alkaloids found in Fuzi are crassicauline A, fuziline, karacoline, and songorine.…”
Section: Introductionmentioning
confidence: 99%